Important Skills for Internship and the Fourth-Year Medical School Courses to Acquire Them: A National Survey of Internal Medicine Residents. (June 2016) - Pereira, Anne G.; Harrell, Heather E.; Weissman, Arlene; Smith, Cynthia D.; Dupras, Denise; Kane, Gregory C.
Abstract : Purpose: To obtain feedback from internal medicine residents, a key stakeholder group, regarding both the skills needed for internship and the fourth-year medical school courses that prepared them for residency. This feedback could inform fourth-year curriculum redesign efforts. Method: All internal medicine residents taking the 2013–2014 Internal Medicine In-Training Examination were asked to rank the importance of learning 10 predefined skills prior to internship and to use a dropdown menu of 11 common fourth-year courses to rank the 3 most helpful in preparing for internship. The predefined skills were chosen based on a review of the literature, a national subinternship curriculum, and expert consensus. Chi-square statistics were used to test for differences in responses between training levels. Results: Of the 24, 820 internal medicine residents who completed the exam, 20, 484 (83%) completed the survey, had complete identification numbers, and consented to have their responses used for research. The three skills most frequently rated as very important were identifying when to seek additional help and expertise, prioritizing clinical tasks and managing time efficiently, and communicating with other providers around care transitions. The subinternship/acting internship was most often selected as being the most helpful course in preparing for internship. Conclusions: These findings indicate which skills and fourth-year medical school courses internal medicine residents found most helpful in preparing for internship and confirm the findings of prior studies highlighting the perceived value of subinternships. Internal medicine residents and medical educators agree on the skills students should learn prior to internship.